2010
DOI: 10.1159/000272046
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Body Exocytosis by Cell Stretch or Purinergic Stimulation: Possible Physiological Roles, Messengers and Mechanisms

Abstract: A major function of the pulmonary alveolar type II cell is the secretion of surfactant, a lipoprotein-like substance, via exocytosis of secretory vesicles termed lamellar bodies (LBs). The process of surfactant secretion is remarkable in several aspects, considering stimulus-delayed fusion activity, poor solubility of vesicle contents, long hemifusion lifetimes, slow fusion pore expansion and active, actin-driven content release. Cell stretch as well as P2Y2 receptor stimulation by extracellular ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 137 publications
(164 reference statements)
1
28
1
1
Order By: Relevance
“…Rotenone is known to inhibit mitochondrial transmembrane potential (ΔΨ) and thus ATP production. ATP induces surfactant secretion binding to purinergic receptors 28. However, in our experiments, this mechanism does not play a relevant role because LB secretion was enhanced and not inhibited after rotenone application.…”
Section: Discussioncontrasting
confidence: 66%
“…Rotenone is known to inhibit mitochondrial transmembrane potential (ΔΨ) and thus ATP production. ATP induces surfactant secretion binding to purinergic receptors 28. However, in our experiments, this mechanism does not play a relevant role because LB secretion was enhanced and not inhibited after rotenone application.…”
Section: Discussioncontrasting
confidence: 66%
“…Within the alveolar lining fluid, ATP might reach millimolar concentrations (58), but the source of it is essentially unknown. Beside a supposed release from scattered purinergic nerve terminals, and release due to cell membrane stress failures, a channel-gated release from AT II cells, as well as a mechanosensitive ATP-exocytosis, has been proposed (16,55). Here, a release of ATP, in concentrations similar to those reported by Patel et al (49) for cyclic stretch, was detected after a brief I AL exposure (ϳ10 s).…”
Section: Discussionmentioning
confidence: 59%
“…Studies on single cells revealed that stretch induces an elevation of the intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) (23,73), perhaps via mechanosensitive ion channels like the wellcharacterized transient receptor potential (TRP) vanilloids (reviewed in Refs. 16,77). Recently, the panoply of mechanosensitive mechanisms was expanded by the finding that the I AL , the "normal" microenvironment of the AT II cells (6), may be a strong mechanical incentive as well.…”
mentioning
confidence: 99%
“…LBs fuse with the plasma membrane in a sequential fashion for up to 20 min after stimulation (23 (25). After LB fusion with the plasma membrane, surfactant, a water-insoluble bulky complex, largely remains entrapped within the fused vesicles (26) in which the fusion pores behave as regulated valves or mechanical barriers for release (16,27).…”
Section: Camentioning
confidence: 99%